Race, social class, and bulimia nervosa - Michelle S. Goeree; John C. Ham; Daniela Iorio (University of Zurich, Department of Economics, 2012)
In this paper we explore a serious eating disorder, bulimia nervosa (BN), which afflicts a surprising number of girls in the US. We challenge the long-held belief that BN primarily affects high income White teenagers, using a unique data set on adolescent females evaluated regarding their tendencies towards bulimic behaviors independent of any diagnoses or treatment they have received. Our results reveal that African Americans are more likely to exhibit bulimic behavior than Whites; as are girls from low income families compared to middle and high income families. We use another data set to show that who is diagnosed with an eating disorder is in accord with popular beliefs, suggesting that African American and low-income girls are being under-diagnosed for BN. Our findings have important implications for public policy since they provide direction to policy makers regarding which adolescent females are most at risk for BN. Our results are robust to different model specifications and identifying assumptions.
Keywords: I1; 330; Bulimia Nervosa; Race; Income; Education; Mädchen; Ernährungsverhalten; Weiße; Farbige Bevölkerung; Einkommen; Schätzung; USA